1993
DOI: 10.1016/0928-8244(93)90016-w
|View full text |Cite
|
Sign up to set email alerts
|

MDHM, a macrophage-activating product of Mycoplasma fermentans, stimulates murine macrophages to synthesize nitric oxide and become tumoricidal

Abstract: In continuation of previous work on macrophage activation by a Mycoplasma fermentans-derived product, originally named "mycoplasma-derived high mol. wt. material" (MDHM), we have investigated whether MDHM was capable of inducing synthesis of the reactive nitrogen intermediate nitric oxide (NO), thus rendering macrophages cytocidal. Mycoplasmas were first delipidated with acetone, and MDHM activity was then extracted with 50 mM 1-O-octyl-beta-D-glucopyranoside to yield a particularly active new preparation of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…MDHM was previously assayed on the basis of its property of inducing from murine macrophages (19). The MDHM-dependent NO generation from IFN--y-primed peritoneal macrophages turned out to be an equally sensitive assay which was at the same time easier to perform in routine tests (21) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDHM was previously assayed on the basis of its property of inducing from murine macrophages (19). The MDHM-dependent NO generation from IFN--y-primed peritoneal macrophages turned out to be an equally sensitive assay which was at the same time easier to perform in routine tests (21) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical characterization of MDHM with such test systems was of necessity slow. We therefore adopted an assay of macrophage activation which was better suited for testing many samples, i.e., the liberation of nitric oxide (NO) from gamma interferon (IFN--y)-treated PECs from endotoxin lowresponder mice (21). MDHM was shown to be active in this system at very high dilutions, inducing at the same time cytocidal activity against tumor necrosis factor (TNF)-resistant P815 tumor cells (21).…”
mentioning
confidence: 99%
“…Past studies of the lipoproteins and related products in Mycoplasma fermentans in our laboratories (11,33,35,36,38,43,(51)(52)(53)59) and by others (15,18,26,40,41) have contributed to the understanding of mycoplasmal surface variation and immunomodulatory activities associated with these surface membrane components. In the present report, we document a novel form of surface variation that involves a previously reported major lipoprotein (P41) and a potent macrophage-activating lipopeptide (MALP-2) of M. fermentans.…”
mentioning
confidence: 96%
“…It has been shown that mycoplasmas, gram-positive wall-less prokaryotes, are able to stimulate the tumoricidal activity of IFN-␥-primed macrophage and that this activity is mediated by TNF-␣ or NO release [6,7]. Accordingly, Yang et al [8] reported that treatment of IFN-␥-primed macrophages with a factor derived from mycoplasmas resulted in cytotoxic activity against a lymphoma T cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial description of a high molecular weight molecule derived from Mycoplasma fermentans, which in combination with IFN-␥ was able to induce the production of NO by murine macrophages [7], attempts were made to isolate and characterize the active principle, which was finally shown to be a lipopeptide [9,10]. Its structure was elucidated and it constitutes one of the most potent macrophage stimulators [11] together with a lipopeptide recently isolated from M. hyorhinis membranes [12].…”
Section: Introductionmentioning
confidence: 99%